Online Business Communication(Quantitative Descriptive Study to the Students of Communications and Informatics Faculty at the Universitas Muhammadiyah Surakarta in 2015) - Dewi, Cintia Puspa; , Dian Purworini, MM; , Nieldya Nofandrilla, S.E., MA (2016)
Cintia Puspa Dewi, L 100112004, ONLINE BUSINESS COMMUNICATION (Quantitative Descriptive Study to the Student of the Communication and Informatics Faculty of thee Universitas Muhammadiyah Surakarta 2015), Thesis, Study Program Of Communication Science, faculty of Communication and Informatics at the Universitas Muhammadiyah Surakarta, 2016 Online businesses are one of business which is now increasingly favored by the majority of Indonesia society. Ease and breadth of coverage makes the online business as a goldmine for young people such as students being able to accept and adapt to new technological developments. The way to communicate become an important factor that is capable of causing the success or failure of an online business. The purpose of this research is to see how online business communication conducted by student of Communication and Informatics Faculty of the Universitas Muhammadiyah Surakarta. This research using quantitative descriptive method, with the aim of describing a social phenomenon that is already exist, detail and systematically. Data collection techniques using questionnaires and questions of explanation as complementary. Sampling technique used in this research is purposive sampling. Criteria of respondent are the minimum monthly income more than two million rupiah and already running online business for one year. Respondent in this research are student of FKI UMS who run the online business totaling 30 people. The results of this study indicate that this form of online business communications used in the form of non-verbal communication, such as text messages, images or emoji to convey persuasive and informative communication message to consumers. In addition, the online media widely used such as social networking sites, online mall, blogs, websites and certain sites in accordance with the characteristics of customers. Promotional efforts is to give a discount on the special day / special events, interactive games and rebates for consumers who are shopping for a nominal amount.